STATUS OF MICROPLASTIC POLLUTION IN AQUATIC ECOSYSTEM WITH A CASE STUDY ON CHERATING RIVER, MALAYSIA - Pariatamby, Agamuthu; Hamid, Fauziah Shahul; Bhatti, Mehran Sanam; Anuar, Norkhairah; Anuar, Norkhairiyah (Journal of Engineering and Technological Sciences, 2020)
Microplastics are emerging contaminants owing to their potential to adsorb and release pollutants from the environment, transferring these pollutants to the food web. Most marine microplastics come from the terrestrial environment, mainly from inland freshwaters that are direct receivers of runoff from urban, industrial, and agricultural areas. The present study investigated the occurrence of microplastics in surface water samples taken from the Cherating river and the Cherating mangrove, Pahang along with a review of recent studies on microplastics abundance in aquatic ecosystems. Three sampling sites were established (two sites along the river and one site in a mangrove in the downstream of the river). In the up- and midstream regions, the river passes by residential, fishery and tourism areas, while the mangrove is located close to Cherating Beach. The highest microplastics abundance was discovered in the midstream region, with an average abundance 0.0070 ± 0.0033 particles/m3, followed by the mangrove (0.0051 ± 0.0053 particles/m3). Fragments with a size of 0.5 to 1.0 mm and white-colored microplastics were prevalent. The findings are similar to those from other microplastic studies (e.g. in Aveiro and Lisbon, Portugal; New England, USA; Kingston Harbour, Jamaica), but lower than microplastics studies in Asia (e.g. Yangtze river estuary and Hangjiang river, China). Overall, the findings provide background information on microplastics pollution in aquatic ecosystems.